The Use of a Parabolic Solar Concentrator in Nasiriya city, Iraq - Hannun, Rafid M.; Koban, Raheem M. (Journal of Petroleum Research and Studies, 2022)
In this paper, it presents a detailed analysis of the use of the parabolic solar concentrator in heating and boiling water, as the parabolic solar concentrator was manufactured with a diameter of (96 cm), the focal length of the dish is (72 cm), and the focus depth of the dish is (8 cm). It was made using a parabolic dish with a diameter of (96 cm) and using glossy aluminum foil as a reflective sun ray after being cut into strips 10 cm wide and glued to the inner surface of the dish. Metal tin cans with two capacities (1L and 2L) were used as the absorbent receiver. Experiments were conducted to boil water from the roof of the house in Nassiriya city. The study calculated the optical efficiency of the equivalent solar concentrator, the amount of heat output as a result of the fall of concentrated solar radiation on the receiver, the amount of useful heat gained, the thermal losses from the receiver, the collector efficiency. Many tests were conducted in Nassiriya city weather conditions. The results of the experiments showed that the efficiency of the solar center mainly depends on the diameter of the concentrator dish, the quality of the reflector used, the time of heating the water, and the closing to midday. While the high ambient air velocity leads to a decrease in the receiver temperature by increasing the heat loses to ambient air by convection, thus reducing the efficiency of the solar concentrator; as well as the accuracy of directing the dish towards the sun and determining the focus accurately also affects the efficiency of the solar concentrator.